2017
DOI: 10.1371/journal.pone.0175553
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-448 suppresses osteosarcoma cell proliferation and invasion through targeting EPHA7

Abstract: Osteosarcoma is the most common type of malignant bone tumor, often affecting adolescents and children. MicroRNAs (miRNAs) are a group of small, non-protein coding, endogenous RNAs that play critical roles in osteosarcoma tumorigenesis. In our study, we demonstrated that miR-448 expression was downregulated in osteosarcoma tissues and cell lines. Overexpression of miR-448 suppressed osteosarcoma cell proliferation, colony formation and migration. Moreover, we found that EPHA7 was a direct target gene of miR-44… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…The finding of miR-885-5p to associate with fetal growth and sperm count also seems to demonstrate an association with development, which fits the developmental model for GCTs [70,71]. Meanwhile, miR-448 has been described as inhibiting cell proliferation and invasion in several tumor models [72][73][74], but its role in this specific context is still unclear. However, despite being of limited use in this specific discrimination, these microRNAs were found to be significantly upregulated in serum samples of patients with teratoma histology when compared to normal males, allowing for a good discrimination among the two groups, which fully confirms the prediction of the in vivo model.…”
Section: Discussionsupporting
confidence: 66%
“…The finding of miR-885-5p to associate with fetal growth and sperm count also seems to demonstrate an association with development, which fits the developmental model for GCTs [70,71]. Meanwhile, miR-448 has been described as inhibiting cell proliferation and invasion in several tumor models [72][73][74], but its role in this specific context is still unclear. However, despite being of limited use in this specific discrimination, these microRNAs were found to be significantly upregulated in serum samples of patients with teratoma histology when compared to normal males, allowing for a good discrimination among the two groups, which fully confirms the prediction of the in vivo model.…”
Section: Discussionsupporting
confidence: 66%
“…Fang et al reported that miR‐188‐5p suppresses tumour cell proliferation and metastasis by directly targeting FGF5 in hepatocellular carcinoma, implying that up‐regulated circMATR3 might sponge miR‐188‐5p and abolish its inhibitory effects on cell proliferation and metastasis. Similarly, Wu et al showed that elevated expression of miR‐448 suppressed osteosarcoma cell proliferation and invasion through targeting EPHA7, indicating that circMATR3 may reverse the inhibitory roles by absorbing miR‐448. Interestingly, miR‐188‐5p and miR‐448 have 3 common targeted mRNAs; among them, USP28 is a famous oncogene that is required for MYC stability in several human tumour cells, while MYC is a central regulator of cell growth, proliferation and apoptosis in many human cancers .…”
Section: Discussionmentioning
confidence: 94%
“…For example, miR‐448 suppressed cell metastasis by modulating the JAK1/STAT3 pathway in pancreatic ductal adenocarcinoma . In addition, miR‐448 was reported to suppress the proliferation and invasion of osteosarcoma cells by inhibiting EPHA7 . Besides that, miR‐448 was found to inhibit EMT by modulating ZEB1/2 in breast cancer .…”
Section: Discussionmentioning
confidence: 99%